SENI TRADISI, JATIDIRI DAN STRATEGI KEBUDAYAAN - Heddy Shri Ahimsa-Putra (Jurnal Ilmu Sosial Mamangan, 2015)
In this article the author identifies and describes three kinds of traditional arts in Indonesia: the arts of the Great Tradition, of the Little Tradition and of the Tribal Tradition. These kinds of tra-ditional arts need to be preserved and developed since they haveÂ  a number of functions for the so-cieties, namely: as tourist attractions; identities of their communities/societies; source of inspira-tions for the creation and development of new arts. In Indonesia, the efforts are hindered by several problems, such as the decline of the popularity of the traditional arts, lack of regeneration, lack of institutional support, and lack of grand design for the development. These problems need to be solved to develop the Indonesian traditional arts.